TECHNOLOGY IN TEACHING SPEAKING SKILL: A REVIEW OF CURRENT LITERATURE - Yahfenel Yahya; Yusrizal Yusrizal; Ridho Kurniawan (Journal Of Language Education and Development (JLed), 2019)
Speaking is one of the skills that have to be mastered by students in learning English. Speaking is an essential tool for communicating. In the classroom, improving the speaking abilities of students has always been a concern. In the fast developing 21st century various innovative technologies are being introduced to teach speaking skill in the classrooms. Technology is the vehicle to get access with this modernized world. More than the process of communication, trade and transactions, today technology is widely used in educational sectors. Technological tools have been regarded as ways of helping students improve language skills such as speaking skill. Internet, podcasts, video conferencing, videos and speech recognition software are considered the best tools for teaching speaking skill. This paper aims to discuss some modern technologies available for teachers of English today to enhance speaking skill of second or foreign language learners.